Crucifixion in the Ancient Art of the Roman Period - Panteleev, Aleksey D. (Actual Problems of Theory and History of Art, 2021)
The article is devoted to the analysis of the representation of the crucifixion in ancient art. Although ancient historians, philosophers, and writers tell a lot about this execution, only a few images correspond to our rich literary tradition. These are 1) a fresco from the Arieti Tomb, or, as it is sometimes called, the Tomb of Magistrates, in Rome (3rd–1st centuries BC); 2) a graffito from Puteoli (early 2nd century AD); 3) and the Alexamenos graffito (the end of the 2nd — the beginning of the 3rd century AD), found during excavations on the Palatine Hill in Rome. The author also examines some artifacts, the authenticity of which in our time is considered questionable. These are a seal-cylinder with Orpheus hanging on a cross and a bone amulet with the image of a crucified ass-headed figure. The rarity of these representations is possibly due to the fact that the Romans from the very beginning considered this ritual barbaric and applicable only to slaves and non-citizens. This topic could not be used to promote imperial ideology or maintain Roman identity. This explains the nature of the majority of the surviving monuments: either graffiti with offensive overtones, or magic gems. The reported study was funded by RFBR, project number 21-011-44180 “The Political Dimension of Early Christian Hagiographic Literature”.